Importance of Integrative Approach in Literature Lessons - Mansurova Malika Askarovna (International Journal on Integrated Education, 2023)
This article focuses on the importance of interdisciplinary integration in teaching literature. The achievements of the integration of literature with other forms of art, such as cinema, theater and music, and the role of computer technology in organizing this process are discussed.